Penalaran Proporsional Siswa SMP dalam Pemecahan Masalah Matematika Ditinjau dari Gaya Kognitif Reflektif dan Impulsif - Fifin Rafina Yunitasari; Susanah Susanah (Universitas Negeri Surabaya, 2026)
Proportional reasoning is a way of thinking in understanding ratios as relationships between quantities, distinguishing between proportional and non-proportional relationships, linking changes in two quantities in an orderly manner, and using multiplication strategies in proportional situations. One factor that influences proportional reasoning is cognitive style. This study is a descriptive study with a qualitative approach that aims to describe the proportional reasoning of junior high school students in solving mathematical problems based on reflective and impulsive cognitive styles. The subjects of this study were two eighth-grade students, each representing reflective and impulsive cognitive styles. Data were collected through mathematical problem-solving task, and task-based interview guidelines. The results showed differences in proportional reasoning activities between reflective and impulsive students. Reflective students identified ratios by writing and interpreting comparisons as representations of relationships between quantities. They recognized proportional relationships by explaining that changes in one quantity were multiples of another and by distinguishing situations that maintained constant ratios from those that did not. Covariation analysis was carried out by systematically linking proportional changes between quantities. In developing informal strategies, reflective students applied unit rates by converting ratios into per-unit forms and using them consistently until the solution was rechecked. In contrast, impulsive students identified ratios by stating comparisons and immediately using them for initial calculations. Proportional relationships were recognized by maintaining fixed ratios during problem solving. Covariation analysis was demonstrated through proportional linking of quantities, although early inaccuracies occurred and were later corrected. The informal strategy most frequently used by impulsive students was the scale factor, determined through multiplication or division, followed by rechecking the results.